The solidarity sector as an alternative for inclusive social development in the Colombian post-conflict - Serna Gómez, Humberto; Rodríguez Barrero, Mario Samuel (Cooperativismo & Desarrollo, 2016)
Purpose: the articles aims to answer the question: How can the social and solidarity economy sector contribute to social and labor inclusion for peacebuilding? Description: in order to answer this question, a summary of the evolution of the cooperative movement is presented, then the current situation of the solidarity economy sector is contextualized and, subsequently, the research proposal under the case method of Cooperativa Prosperando is described as an example. Point of view: one of the factors that has given rise to the conflict is the social problem of poverty and inequality in our country, and the application of the solidarity economy principles can be a viable solution to improve the condition of thousands of Colombians. Therefore, it is important that these matters be addressed not only in the academic sphere, but that they transcend politically and governmentally and, above all, that they come true. Conclusions: it is concluded that associations, social inclusion and civil economy, as part of the solidarity economy sector, are essential for reconciliation and peace strengthening in a Colombian post-conflict scenario.